Effect of Acupuncture Combined with Enriched Rehabilitation Training on Neural Function, Nogo Protein and Its Receptor in Cerebral Ischemia Rats - Mengxing LI; Zhaohui CHEN; Qi LIU; Fang LIU; Wei TANG (康复学报)
Objective:To explore the effect of acupuncture combined with enriched rehabilitation training on the neural function, the study would observe the regulation of nerve regeneration inhibiting factor (Nogo-A) and Nogo receptor (NgR) in cerebral ischemia rats.Methods:Healthy male SD rats were randomly divided into operation group and sham operation group. Cerebral ischemia model of middle cerebral artery occlusion (MCAO) was established in rats by using the external carotid artery embolism. Four hours after the surgery, 96 rats of one to three points of NIHSS were selected and divided into the model group, the acupuncture group, the enriched rehabilitation training group and the acupuncture combined with enriched rehabilitation training group, and 24 rats in each group. The scores of neural function deficit, sensation and motor ability were recorded, and the expression of Nogo-A and NgR proteins in hippocampal tissues were detected by immunohistochemistry staining.Results:At the 7 d, 14 d after treatment, the neural function deficit score, sensation and motor ability score in the acupuncture group, the enriched rehabilitation training group and the acupuncture combined with enriched rehabilitation training group were lower respectively than those of the model group (P<0.01 or P<0.05), and the scores in the acupuncture combined with enriched rehabilitation training group were lower respectively than those of the acupuncture group and the enriched rehabilitation training group (P<0.01 or P<0.05). The expression of Nogo-A and NgR proteins in the model group, the acupuncture group, the enriched rehabilitation training group and the acupuncture combined with enriched rehabilitation training group were higher respectively than those of the sham operation group (P<0.01 or P<0.05), the proteins expression in the acupuncture group, the enriched rehabilitation training group and the acupuncture combined with enriched rehabilitation training group were lower respectively than those of the model group (P<0.01 or P<0.05), and the proteins expression in the acupuncture combined with enriched rehabilitation training group were lower respectively than those of the acupuncture group and the enriched rehabilitation training group (P<0.01 or P<0.05).Conclusion:Acupuncture combined with enriched rehabilitation training can improve hippocampal pathological damage induced by cerebral ischemia, and promote the recovery of sensory and motor functions. Additionally, the effect of acupuncture combined with enriched rehabilitation training is superior to that of simple acupuncture or simple rehabilitation training.